No association of BRD1 and ZBED4 polymorphisms with schizophrenia in the Chinese Han population. (August 2018) - Xu, Fei; Bi, Yan; Ren, Decheng; Zhu, Yuhao; Hu, Jiaxin; Yuan, Fan; Yuan, Ruixue; Ma, Gaini; Niu, Weibo; Guo, Zhenming; Sun, Qianqian; Wu, Xi; et al.
Abstract : The distal long arm of chromosome 22 (22q13.3) may harbor genes implicated in schizophrenia. This is evidenced by various genetic mapping studies. BRD1 and its neighboring gene ZBED4, both located within this region, have repeatedly been found to be associated with schizophrenia in the Caucasian population. In this study, we chose seven SNPs (two BRD1 SNPs, five ZBED4 SNPs) to carry out an association study between these two genes and schizophrenia in the Chinese population. However, no significant result was obtained, which was consistent with the Japanese population. Taken together, we could conclude that BRD1 and ZBED4 might be population specific in schizophrenia and may not account for a substantial proportion of genetic risk for schizophrenia in the Asian population.